Entrepreneurship: A Way to Mitigate Unemployment (International Journal of Food and Nutritional Sciences, 2019)
In most developing nations, rising unemployment has replaced falling living standards as theprimary barrier to poverty. As a result of the per capita income's sharp decline, the poor aregetting poorer. Even those who are literate struggle to make enough money to meet theirrequirements and are either underemployed or unemployed.